2015
DOI: 10.1007/s00198-015-3186-y
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcopenic obesity is associated with reduced handgrip strength, walking abilities, and balance in postmenopausal women

Abstract: These findings indicate a poorer functionality in women presenting with OSO, particularly compared to OB women, increasing the risk for bone fractures and immobility from the combined decline in bone and muscle mass, and increased fat mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
90
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 34 publications
7
90
1
2
Order By: Relevance
“…We showed recently that older women suffering from osteopenic obesity, sarcopenic obesity and/or osteosarcopenic obesity (as an ultimate fate of former two) were inferior in several of the functional performance measures, compared to their obese-only counterparts. Even more so, those suffering from osteosarcopenic obesity showed significantly poorer performance in handgrip strength, balance and walking speed, compared to each other group (Ilich et al 2015).…”
Section: :1mentioning
confidence: 86%
See 4 more Smart Citations
“…We showed recently that older women suffering from osteopenic obesity, sarcopenic obesity and/or osteosarcopenic obesity (as an ultimate fate of former two) were inferior in several of the functional performance measures, compared to their obese-only counterparts. Even more so, those suffering from osteosarcopenic obesity showed significantly poorer performance in handgrip strength, balance and walking speed, compared to each other group (Ilich et al 2015).…”
Section: :1mentioning
confidence: 86%
“…Recently, some researchers and fitness professionals used body fat of 32% as the cutoff for overweight/obesity in women , Wanner et al 2016. In other studies, the 35% body fat as a cutoff was used for obesity classification (Ilich et al 2015) and that of 33% and/or 38% showed adverse influence on various skeletal sites . With an increased awareness of body fat causing derangements at many levels, we recommend a lower cutoff for obesity for women, specifically, 32-35% of body fat, than currently proposed by WHO (40%).…”
Section: :1mentioning
confidence: 99%
See 3 more Smart Citations